The high frequency of alcohol advertising during televised English Premier League football games shown in Ethiopia - Mulugeta Tamire; Alex Barker; Sefonias Getachew; Rachael L. Murray; Rihanna Amedala; John Britton; Wakgari Deressa; Andrew W. Fogarty (BMC, 2022)
Abstract Background Excessive alcohol consumption is an important risk factor for increased morbidity, mortality and other social harms globally. Televised sport allows the promotion of alcoholic drinks to a large and often young audience, and thus can be used to develop new markets for alcohol in low- and middle-income countries. This study aimed to analyse the alcohol advertising displayed during televised English Premier League (EPL) games, which is widely viewed in Ethiopia, and are particularly popular among young people. Methods Nineteen live televised EPL football matches broadcast in Ethiopia on the SuperSport channels over 4 weeks of the 2018/19 season were digitally recorded from the digital satellite television. Exposure to alcohol advertising was measured by calculating the total elapsed time duration with the alcohol content from the pre-match to the end of the post-game period of the broadcast. Results Data were available for a total of 2451 min broadcast time. Alcohol advertising accounted for 205.2 min (8.4%) with a mean duration of 10.8 min per match (range 5.5 to 22.6). The dominant format of alcohol advertisement was the display of logos associated with an alcoholic drink on the television (TV) screen, which accounted for approximately 43% of the total alcohol advertising time. This was followed by pitch side virtual display (17.7%) and a glass of alcohol drink on the TV screen (17.6%). Over three quarters of alcoholic drink advertising (77.7%) was during active football playing time. None of the advertisements on the televised football games showed cigarettes. Conclusion There is a high frequency of exposure to alcohol advertising during televised EPL matches in Ethiopia. It is important to ensure that the newly introduced domestic ban on alcohol advertising is also applied to foreign satellite broadcasters. This is likely to have relevance to other sub-Saharan African countries in promoting public health strategies to reduce harm from alcohol consumption.